2009
DOI: 10.1002/cbic.200800678
|View full text |Cite
|
Sign up to set email alerts
|

Specific Labeling of Peptidoglycan Precursors as a Tool for Bacterial Cell Wall Studies

Abstract: Because of its importance for bacterial cell survival, the bacterial cell wall is an attractive target for new antibiotics in a time of great demand for new antibiotic compounds. Therefore, more knowledge about the diverse processes related to bacterial cell wall synthesis is needed. The cell wall is located on the exterior of the cell and consists mainly of peptidoglycan, a large macromolecule built up from a three-dimensional network of aminosugar strands interlinked with peptide bridges. The subunits of pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 100 publications
(88 reference statements)
0
24
0
Order By: Relevance
“…A key factor of the efficacy of carbapenems is their ability to bind to multiple different PBPs (81). Since cell wall formation is a dynamic "three-dimensional process" with formation and autolysis occurring at the same time, when PBPs are inhibited, autolysis continues (237). Eventually the peptidoglycan weakens, and the cell bursts due to osmotic pressure.…”
Section: In the Beginning…mentioning
confidence: 99%
“…A key factor of the efficacy of carbapenems is their ability to bind to multiple different PBPs (81). Since cell wall formation is a dynamic "three-dimensional process" with formation and autolysis occurring at the same time, when PBPs are inhibited, autolysis continues (237). Eventually the peptidoglycan weakens, and the cell bursts due to osmotic pressure.…”
Section: In the Beginning…mentioning
confidence: 99%
“…The development of novel PG acting agents has lagged; however, because our overall knowledge of PG biosynthesis and turnover is still very limited 2,3 . This is due, in part, to the lack of tools or methods to enable real-time spatiotemporal tracking of PG biosynthesis in live bacterial cells 4,5 . Recently, we have shown that fluorescently modified D-amino acids enable rapid and covalent detection of cell wall biosynthesis, in real time, in live cells, and in a broad range of bacterial species 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The development of tools and methods to enable real-time tracking of the progression of cell wall biosynthesis and peptidoglycan recycling is a problem of significant current interest for which there was no general solution 4,5 . Methods relying on fluorescently-labeled antibiotics such as vancomycin, with high affinity for nascent PG, have had a profound impact on the field, but these methods also have some inherent limitations 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Lipid II carries the basic PG monomer composed of GlcNAc and MurNAc-pentapeptide. Next, lipid II is flipped across the membrane, the PG monomer is cleaved of the undecaprenyl phosphate and incorporated into the growing chain [2][4].…”
Section: Introductionmentioning
confidence: 99%